Older adults with functional limitations and their use of telehealth during COVID-19 - Kim, Yijung K. (2023)
We investigated the association between functional limitations and telehealth use among older Medicare beneficiaries in 2020. We use logistic regression models to estimate associations between functional limitations and the use of technological tools (i.e., computers, Internet, telehealth). We consider Internet use and informal technological support as moderators for telehealth use. Respondents (N = 3151; Mage = 78.31) with more functional limitations were more likely to use video-based telehealth. Net of functional limitations, those with a consistent Internet use were more likely to use emails/texts/portal messages to communicate with a healthcare provider. Further, more functional limitations were associated with a higher probability of using emails/texts/portal messages, but only among respondents who received informal technological support. Healthcare access may have been more difficult for older adults with functional limitations during the COVID-19 pandemic, especially for those with little prior experience with the Internet, or those without friends/family to provide technological support.